Offering honey containing a selective insecticide as food for pests and parasitoids: another effective use. (9th March 2016) - Uefune, M.; Nakashima, Y.; Takabayashi, J.; Urano, S.; Kugimiya, S.; Shimoda, T.
Abstract: We investigated the effects of the presence of a selective insecticide, pyridalyl, in aqueous solutions of honey as food for adults of diamondback moth (DBM) Plutella xylostella (L.) and its larval parasitoid Cotesia vestalis (Halliday) on their performances. We used a commercial formulation of pyridalyl which contained 10% pyridalyl. Survival times of DBMs reared with honey solution with pyridalyl at 10 000‐fold dilution were not significantly different from those of DBMs reared with pure honey solution. However, at 1000‐fold and 100‐fold dilutions of pyridalyl in honey solution, survival times were significantly shorter than those with honey solution alone. By contrast, survival times of C. vestalis reared with honey solution with pyridalyl at 1000‐fold and 100‐fold dilution were not significantly different from those of C. vestalis reared with pure honey solution. Offering honey solution with pyridalyl at 100‐fold dilution to C. vestalis did not affect its parasitization ability or offspring sex ratio. The novel aspects of the use of selective pesticides to control DBMs using C. vestalis are discussed.